Key Attributes and Potential Barriers of Long-Term Care Administration Programs : A Ten-Year Analysis of NAB Accreditation Reports - Olson, Douglas M.; Johs-Artisensi, Jennifer L.; Schwaller, Alyssa (My University, 2018)
The purpose of this study was to identify what components are necessary to create a strong long term care administration program.
Color poster with text and images.
Keywords: Accreditation (Education); National Association of Long-Term Care Administration Boards; Administration; School accreditation; Posters